1998
DOI: 10.1159/000013974
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activation during the Early Neonatal Period

Abstract: The first week of life is a time when hereditary or more frequently acquired factors lead to some important differences in the hemostatic mechanism of the newborn. It has been well known that ill neonates are prone to both hemorrhage and thrombosis. The aim of this study was to answer the question of whether there is a difference in platelet activation in healthy neonates during the first days of life that may contribute to both hemorrhage and thrombosis in the presence of additional pathologic insults. Platel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
3
3
0
Order By: Relevance
“…The neonatal platelet phenotype differs from that of adults in-vitro , exhibiting hypoaggregability with many commonly used agonists such as ADP, epinephrine, thrombin, and thromboxane analogs (Mull and Hathaway, 1970 ; Israels et al, 1990 ; Rajasekhar et al, 1994 ). Platelet preactivation during accouchement and resultant refractoriness has been proposed, but in agreement with other research groups we found no increase in activation markers on neonatal platelets after delivery (Nicolini et al, 1994 ; Grosshaupt et al, 1997 ; Irken et al, 1998 ). Instead, multifactorial impairments in signal transduction of neonatal platelets have been shown to cause hyporeactivity.…”
Section: Introductionsupporting
confidence: 93%
“…The neonatal platelet phenotype differs from that of adults in-vitro , exhibiting hypoaggregability with many commonly used agonists such as ADP, epinephrine, thrombin, and thromboxane analogs (Mull and Hathaway, 1970 ; Israels et al, 1990 ; Rajasekhar et al, 1994 ). Platelet preactivation during accouchement and resultant refractoriness has been proposed, but in agreement with other research groups we found no increase in activation markers on neonatal platelets after delivery (Nicolini et al, 1994 ; Grosshaupt et al, 1997 ; Irken et al, 1998 ). Instead, multifactorial impairments in signal transduction of neonatal platelets have been shown to cause hyporeactivity.…”
Section: Introductionsupporting
confidence: 93%
“…It has been argued that degranulation of neonatal platelets occurs during delivery and that platelets become refractory and consequently hyporesponsive to potent agonists. However, in agree-ment with other research groups we could find no signs of partial activation of neonatal platelets during delivery (11)(12)(13).…”
Section: Introductionsupporting
confidence: 92%
“…34 More recent studies using flow cytometric measurements of activation markers found no increase in the numbers of circulating degranulated platelets in either the fetus or the neonate, and the mode of delivery did not influence these findings. 67,69,70,[73][74][75] The hyporesponsiveness of neonatal platelets therefore does not appear to be the result of partial activation or degranulation during labor or delivery.…”
Section: Platelet Activation During Deliverymentioning
confidence: 99%